How do you simplify (x^2 + 3x + 10)(4x^2 - 2x - 7)?

1 Answer
Jul 17, 2018

=4x^4+10x^3+27x^2-41x-70

Explanation:

Each term in the first bracket has to be multiplied by each term in the second bracket.

(color(red)(x^2) +color(blue)(3x)+color(green)(10))(4x^2-2x-7)

=color(red)(x^2)(4x^2-2x-7) +color(blue)(3x)(4x^2-2x-7)+color(green)(10)(4x^2-2x-7)

=color(red)(4x^4-2x^3-7x^2) +color(blue)(12x^3-6x^2-21x)+color(green)(40x^2-20x-70)

Now simplify by collecting the like terms,

=(4x^4)+(-2x^3+12x^3)+(-7x^2-6x^2+40x^2)+(-21x-20x)+(-70)

=4x^4+10x^3+27x^2-41x-70